Back Cover: Origin of the Superior Performance of (Thio)Squaramides over (Thio)Ureas in Organocatalysis (Chem. Eur. J. 45/2013). Issue 45 (23rd October 2013) - Lu, Tongxiang; Wheeler, Steven E.
<x xml:space="preserve">Abstract</x> Squaramides are widely recognized as superior dual‐hydrogen‐bonding elements compared to (thio)ureas and have found many applications in the fields of molecular recognition and organocatalysis. In their Full Paper on page 15141 ff., T. Lu and S. E. Wheeler demonstrate that thiosquaramides provide even stronger hydrogen‐bonding interactions and propose a thiosquaramide‐based aminocatalyst for the asymmetric Diels–Alder cycloaddition of nitroalkenes to anthracene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>